Integrated Organic Farm; a model aimed at contributing to food security for indigenous communities in Talamanca - Salazar-Díaz, Ricardo (2015)
This project takes place under the context of the Inter-Universitarian Regional Development Initiative - Strengthening of the indigenous productive systems and marketing of the outsourcing and productive indigenous services, as well as respecting the Bribri and Cabécar cultures, within an environmentally sustainable approach. This project focuses on a model of an integrated organic farm, aimed to contribute to food security, agro-ecological practices and culture strengthening of indigenous communities in Talamanca. The project is led by three young brothers from the community of Shuabb, Telire, Talamanca. In an area of four acres, a model of agricultural production was established, which basically consists in agriculture and livestock of minor species diversification. Over twenty different kinds of species of crops were planted, among roots, tubers, vegetables, cereals, fruits, and grains. Free range chickens and pigs as well as fish ponds have turned this family farm into an alternative model of economic development, contributing to self-sufficient consumption and promoting local market. Traditional farming in Talamanca comes from the continuous and balanced relationship between humans and their natural environment; however, there is evidence of deterioration in this relationship. As a result of this initiative, this proposal intends to be a model to be replicated in neighboring communities and so contribute to sustainable human development in the region of Talamanca.